Reconfigurable embedded control systems : applications for flexibility and agility - Khalgui, Mohamed; Hanisch, Hans-Michael. (Hershey, PA : Information Science Reference, 2011)
"This book addresses the development of reconfigurable embedded control systems and describes various problems in this important research area, which include static and dynamic (manual or automatic) reconfigurations, multi-agent architectures, modeling and verification, component-based approaches, architecture description languages, distributed reconfigurable architectures, real-time and low power scheduling, execution models, and the implementation of such systems"--
Includes bibliographical references and index.
Keywords: Programmable controllers; Embedded computer systems; Digital control systems